FRI0496 Efficacy and Safety of Canakinumab in Children with Systemic Juvenile Idiopathic Arthritis with and Without Fever. (9th June 2015) - Ruperto, N.; Brunner, H.; Quartier, P.; Constantin, T.; Alexeeva, E.; Kone-Paut, I.; Marzan, K.; Wulffraat, N.; Schneider, R.; Padeh, S.; Chasnyk, V.; Wouters, C.; et al.
Abstract : Background: Canakinumab (CAN) leads to improvement for patients (pts) with systemic juvenile idiopathic arthritis (SJIA) 1 . However, little is known about potential differences in response to CAN treatment between pts with vs. without SJIA associated fever at the time of the first CAN administration. Objectives: To evaluate the long-term efficacy and safety profile of CAN-naïve children with SJIA pts with and without SJIA associated fever. Methods: Pts aged 2-20 yrs with SJIA with and without SJIA associated fever at enrollment received open-label CAN 4mg/kg s.c. every 4 wks. Every 3 months, response to CAN was measured by adapted JIA ACR response criteria (aACR/JIA); juvenile arthritis disease activity score [JADAS]; clinical inactive disease; clinical remission on medication [6 months continuous clinical inactive disease]. Safety was assessed monthly. Results: Data on 122/267 pts, 53 (43%) with and 69 (57%) without SJIA associated fever, were available for analysis with a median 94 wk study duration. At Wk4, ∼75% of both subgroups had responded (≥aACR/JIA30), increasing to 90% at Wk12. At Wk2, ∼21% of both subgroups had inactive disease; 44% at Wk8; 60% at Wk20 and then 60-70% for the remainder of the trial. Clinical remission on medication was achieved in about 29% of pts in both subgroups with ∼22% maintaining it for ≥12 consecutive months. At baseline, the median JADAS score was 21.5 with 8 (7.5%) and 99 (92.5%) pts meeting the criteria for moderate (JADAS >3.8 and ≤10.5) and high disease activity (JADAS >10.5), respectively. At Day15, the median JADAS was 6.8 and 1.5 at the last assessment. In addition, at the last assessment, 53 (48%) pts were rated as inactive disease (JADAS ≤1); 10 (9%) with low active disease activity (JADAS >1 and ≤3.8); while 14 (13%) had moderate and 31 (28%) with high disease activity. A similar long-term safety profile to the pivotal program in children with fever at enrollment was observed in these CAN-naïve pts with or without fever. The most common type of adverse event (AE) reported was infection (0.56 infections/100 PT-days) typically involving the upper respiratory tract. Fifteen pts discontinued due to an AE and 40 had >1 SAE (mostly infections, macrophage activation syndrome [MAS], or flare-associated) and no deaths. Eight cases of MAS (0.013 events/100 pt-days) were reported. Conclusions: Canakinumab provides similar efficacy (inactive disease, clinical remission) in SJIA pts with and without SJIA associated fever at treatment onset. The long-term safety profile was acceptable and similar to the pivotal program in SJIA children with fever at enrollment. References: Ruperto et al. N Engl J Med. 2012; 367: 2396-406. Disclosure of Interest: N. Ruperto Grant/research support from: Abbott, Bristol Myers and Squibb, Francesco Angelini S.P.A., Glaxo Smith & Kline, Janssen Biotech Inc Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH: I declare that the GASLINI Hospital which is the public Hospital where I work as full time employee has received contributions to support the research activities of the network of PRINTO, Consultant for: Bristol Myers and Squibb, Centocor Research & Development, Glaxo Smith & Kline, Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH, I declare that the Gaslini Hospital which is the public Hospital where I work as full time employee has received contributions to support the PRINTO research activities from the industries above mentioned, Speakers bureau: Abbott, Abbvie, Amgen, Astellas, Biogenidec, Boehringer, Bristol MyersSquibb, Celgene, CrescendoBio, EMD Serono, Italfarmaco, Janssen, MedImmune, Novartis, NovoNordisk, Pfizer, Reumatic.com, Roche, Sanofi, Servier, Sinergie, Takeda, H. Brunner Consultant for: Novartis, Genentech, Pfizer, UCB, AstraZeneca, Biogen, Boehringer-Ingelheim, Regeneron, Speakers bureau: Novartis, Genentech, P. Quartier Grant/research support from: Abbvie, BMS, Chugai-Roche, Novartis, Pfizer, SOBI, Consultant for: Abbvie, Novartis, Servier, SOBI, Speakers bureau: Abbvie, BMS, Chugai-Roche, Medimmune, Novartis, Pfizer, SOBI, T. Constantin Consultant for: Pfizer, Abbvie, Roche, Novartis, Bristol-Myers Squibb, Speakers bureau: Pfizer, Abbvie, Roche, Novartis, Bristol-Myers Squibb, E. Alexeeva Grant/research support from: Roche, Abbott, Pfizer, Bristol-Myers Squibb, Centocor, Novartis, Speakers bureau: Roche, Merck Sharp &Dohme, Abbott, Bristol-Myers Squibb, Medac, Novartis, Pfizer, I. Kone-Paut Grant/research support from: To my institution: SOBI, Roche, Novartis, Consultant for: Novartis, SOBI, Pfizer, CHUGAI, Abbvie, K. Marzan Grant/research support from: Novartis and Abbvie, Employee of: University of Southern California, N. Wulffraat Grant/research support from: Novartis, Pfizer, Abbvie, SOBI, Consultant for: Novartis, Pfizer, SOBI, R. Schneider Consultant for: Novartis, Roche, S. Padeh: None declared, V. Chasnyk: None declared, C. Wouters Grant/research support from: Unrestricted grant support GSK, Novartis, Roche, J. Kummerle Deschner Grant/research support from: Novartis, Consultant for: Novartis, T. Kallinich Speakers bureau: Novartis, BMS and Pfizer, B. Lauwerys: None declared, E. Haddad: None declared, E. Nasonov: None declared, M. Trachana Grant/research support from: Abbvie, Novartis, Pfizer, Consultant for: Novartis, Pfizer, Roche, Speakers bureau: Novartis, Pfizer, Roche, O. Vougiouka Grant/research support from: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, K. Leon Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, A. Martini Grant/research support from: The Gaslini Hospital, which is the public Hospital where I work as a full time employee, has received contributions to support the research activities of the network of PRINTO from Bristol Myers and Squibb, Glaxo Smith & Kline, Janssen Biotech Inc, Novartis, Pfizer, Roche, Schwartz Bioscences GmbH, Speakers bureau: AbbVie, Boerhinger, Celgene, CrescendoBio, Janssen, Meddimune, Novartis, NovoNordisk, Pfizer, Sanofi Aventis, Vertex, Servier, D. Lovell Grant/research support from: National Institutes of Health, Consultant for: Astra-Zeneca, Bristol Meyers Squibb, AbbVee, Pfizer, Roche, Novartis, UBC, Forest Research Institute, Horizon, Johnson & Johnson, Biogen, Takeda, Genentech, Glaxo Smith Kline, Boehringer Ingelheim, Celgene, Jannsen, Speakers bureau: Genentech, Roche, Novartis